Characterizing black carbon in rain and ice cores using coupled tangential flow filtration and transmission electron microscopy - Ellis, A.; Edwards, R.; Saunders, M.; Chakrabarty, R.; Subramanian, R.; Van Riessen, Arie; Smith, A.; Lambrinidis, D.; Nunes, L.; Vallelonga, P.; Goodwin, I.; Moy, A.; et al. (Copernicus GmbH, 2015)
Antarctic ice cores have been used to study the history of black carbon (BC), but little is known with regards to the physical and chemical characteristics of these particles in the remote atmosphere. Characterization remains limited by ultra-trace concentrations in ice core samples and the lack of adequate methods to isolate the particles unaltered from the melt water. To investigate the physical and chemical characteristics of these particles, we have developed a tangential flow filtration (TFF) method combined with transmission electron microscopy (TEM). Tests using ultrapure water and polystyrene latex particle standards resulted in excellent blanks and significant particle recovery. This approach has been applied to melt water from Antarctic ice cores as well as tropical rain from Darwin, Australia with successful results: TEM analysis revealed a variety of BC particle morphologies, insoluble coatings, and the attachment of BC to mineral dust particles. The TFF-based concentration of these particles has proven to give excellent results for TEM studies of BC particles in Antarctic ice cores and can be used for future studies of insoluble aerosols in rainwater and ice core samples.